Changes in the subjective assessment of quality of life in Latvia and the European Union: results of European quality of life survey 2016 - Kristapsone, Silvija; Bruna, Silvija (University of Latvia, 2019)
Assessment of quality of life covers a variety of areas - economic conditions, housing, local environment, employment, education, household structure and family relations, work-life balance, health and healthcare, subjective well-being, quality of society. The assessment of quality of life does not always coincide with the macroeconomic indicators of the country, e.g. GDP. It includes a number of subjective indicators, which frequently show a different situation and trends than the macroenomic indicators. The European Quality of Life Survey (EQLS) is a tested tool of monitoring and analysing the quality of life in the EU and is seeing its fourth issue in 2016. The purpose of this article is to inspect changes in individual subjective well-being indicators among the Latvian society, as presented in the EQLS 2016 in the context of the EU countries, comparing to the EQLS results for 2011-2012. The following tasks were set to achieve that goal: 1) provide an insight into the current understanding of and problems relevant to the concept of quality of life and subjective well-being, 2) analyse the data resulting from the EQLS 2016, as opposed to the data of the EQLS 2011-2012, in Latvia and in the EU countries in general. Methods of descriptive and inferential statistical analysis used in the study. The sources of information used are the European Foundation for the Improvement of Living and Working Conditions databases for 2011-2012 and 2016, available from the UK Data Archive. Conclusions from the statistical analysis: Comparison between the indicators for Latvia and the average for the EU in both 2016 and 2011 revealed a lower self-assessment of well-being, on a scale of 10, among the residents of Latvia than among those of the EU in general. In the EU, seven out of eight of the selected subjective well-being elements retained the same assessment level as in 2011. In Latvia, the assessment dropped in 6 indicators. Only one indicator increased both in the EU and Latvia, and that is the satisfaction with the present state of the economy in country. On the subjective well-being ratings of the EU, Latvia places 21st (Satisfaction with education, Satisfaction with job and Satisfaction with the present state of the economy in country) to 28th (Satisfaction with accommodation). The EQLS data shows that the economic growth, social and economic reforms, social security efficiency in the surveyed five years of post-crisis in the EU have not significantly contributed to their personal assessment of quality of life.
Keywords: Quality of life; subjective well-being; life satisfaction; Research Subject Categories::SOCIAL SCIENCES::Business and economics